Long-Term Prophylaxis and Pharmacokinetic Evaluation of Intramuscular Nano- and Microparticle Decoquinate in Mice Infected with P. berghei Sporozoites. (13th April 2017) - Li, Qigui; Xie, Lisa; Caridha, Diana; Zeng, Qiang; Zhang, Jing; Roncal, Norma; Zhang, Ping; Vuong, Chau; Potter, Brittney; Sousa, Jason; Marcsisin, Sean; Read, Lisa; et al.
Abstract : Decoquinate nanoparticle and microparticle suspended in an oily vehicle to retard drug release are evaluated for long-term malaria prophylaxis. Pharmacokinetic studies in normal animals and antimalarial efficacy in liver stage malaria mice were conducted at various single intramuscular-decoquinate doses for 2, 4, 6, or 8 weeks prior to infection with P. berghei sporozoites. The liver stage efficacy evaluation was monitored by using an in vivo imaging system. Full causal prophylaxis was shown in mice with a single intramuscular dose at 120 mg/kg of nanoparticle decoquinate (0.43  μ m) for 2-3 weeks and with microparticle decoquinate (8.31  μ m) injected 8 weeks earlier than inoculation. The time above MIC of 1, 375 hr observed with the microparticle formulation provided a 2.2-fold longer drug exposure than with the nanoparticle formulation (624 hr). The prophylactic effect of the microparticle formulation observed in mice was shown to be 3-4 times longer than the nanoparticle decoquinate formulation.